2022
DOI: 10.1007/s10909-022-02684-1
|View full text |Cite
|
Sign up to set email alerts
|

Circulation of Superfluid Suction Vortex

Abstract: Although the suction vortex is the one of the most common vortices, its flow structure has not been fully understood. The main reasons for this are the experimental difficulty due to the very rapid flow change near the core. However, superfluid helium may help us better understand the suction vortex, because the flow in the superfluid helium can be characterized by the circulation measured by the first sound velocity, and the configuration of the quantized vortex lines can be measured with the second sound att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…It is worth noting that larger circulation values around a draining vortex in He II are documented in the literature 41 . However, therein, the contributions of the vortex core and the solid-body rotation are not distinguished.…”
Section: Mainmentioning
confidence: 89%
See 1 more Smart Citation
“…It is worth noting that larger circulation values around a draining vortex in He II are documented in the literature 41 . However, therein, the contributions of the vortex core and the solid-body rotation are not distinguished.…”
Section: Mainmentioning
confidence: 89%
“…State-of-the-art numerical models 38 account for the motion of vortex lines coupled to the superfluid and normal velocity fields, but fail to dynamically model the interface, which is a pivotal element in our system. Previous experimental efforts [39][40][41] confirmed that a draining vortex in He II carries macroscopic circulation but lacked spatial resolution required to investigate central confinement of rotational components. In this regard, cryogenic flow visualization 42 provides sufficient resolution.…”
mentioning
confidence: 99%
“…It is worth noting that larger circulation values around a draining vortex in He II are documented in literature [37]. However, therein the contributions of the vortex core and the solid body rotation are not distinguished.…”
mentioning
confidence: 91%
“…State-of-the-art numerical models [34] account for the motion of vortex lines coupled to the superfluid and normal velocity fields, but fail to dynamically model the interface, which is a pivotal element in our system. Previous experimental efforts [35][36][37] confirmed that a draining vortex in He II carries macroscopic circulation, but lacked spatial resolution required to investigate central confinement of rotational components. In this regard, cryogenic flow visualisation [38] provides sufficient resolution.…”
mentioning
confidence: 99%